Dbanie o własne zdrowie w opinii nauczycieli pracujących z uczniami z niepełnosprawnością intelektualną w szkołach ogólnodostępnych = The opinion of public school teachers who work with mentally disabled pupils about how they care of their health - Kataryńczuk-Mania, Lidia; Korzeniowska, Regina (Vilnius: Mykolas Romeris Universitetas)
Education of children and teenagers does not only require modern teachers to have sufficient qualification, competencies and abilities but it calls for awareness of potential difficulties and solutions for them as well. It is a particular challenge for them to work with mentally disabled children. Such teacher should be a committed and creative specialist with comprehensive knowledge who knows how to deal with stress, challenges and to care about his or her health.
Keywords: stres zawodowy; zachowania prozdrowotne; dbałość o zdrowie; nauczyciel uczniów z niepełnosprawnością intelektualną; uczeń z niepełnosprawnością intelektualną; occupational stress; health-promoting activities; healthcare; mentally disabled children teacher; mentally disabled pupil